Can HPV testing be the sole primary cervical screening modality? - Cuzick, Jack (Henry Stewart Talks, 2010)
Cases of cervical cancer in the UK, Potential role of HPV testing in cervical screening, Baseline results of HPV testing in European and North American screening studies, HPV positivity by age, Cytology sensitivity and positivity, HPV sensitivity and positivity, Double-testing studies, Randomized trials, Long-term follow-up of HPV testing: results from the Hammersmith study, Proposed new screening algorithm, HPV typing, mRNA testing, Other potential adjunctive tests, Potential future screening algorithm
Archived at 2017/12/31